Guardian Gate: A Smart, Sensor-Based Entry System with Arduino - R, Mohan Raj K; R, Neharika; M, Ragavarshini (IRO Journal on Sustainable Wireless Systems, 2024)
Addressing the need for enhanced convenience and security in home entry systems, the 'Guardian Gate' utilizes multiple sensors and output devices with Arduino Uno microcontroller technology. This system uses an infrared (IR) sensor as its main input mechanism to detect the presence of people or objects approaching the door. The system warns the homeowner by turning on multiple output devices, such as an LCD screen for visual feedback, an LED indication for visual cues, and a buzzer for auditory alerts, when an object is identified within the predetermined range. Because of its modular architecture, which enables smooth integration and adaptation to suit various household situations, the system is highly versatile and may be used either alone or in conjunction with pre-existing home automation systems. Regardless of their immediate surroundings or activities, users will always be instantly aware of any activity at their door thanks to our multi-sensory method.
Keywords: Automation; home security; accessibility; adaption; intruders